POLISH POSTCOLONIALITY IN A DISTORTING (?) MIRROR THE JOURNALISM OF RAFAŁ ZIEMKIEWICZ - Nakoneczny, Tomasz (Porównania, 2015)
The article is devoted to the problem of Polish postcoloniality in terms of Rafał Ziemkiewicz, one of the most influential Polish writers and journalists of the middle generation. Ziemkiewicz believes that the social structure and mentality of contemporary Poles have been entirely determined by the Second World War and communism. The society, which appeared as a result, is something completely new in history. What unites this society with the past is only a heritage of feudal and colonial dependency. Ziemkiewicz believes that the opportunity to overcome this heritage gives reference to the tradition of organic work and national democracy. He resigns from the characteristic of the Polish intelligentsia overview of reality through the prism of ideology. He is much closer to the tradition of the Anglo-Saxon conservatism and re-publicanism, based on the ideals of freedom, respect for tradition and compromise. The author of the article tries to show the thought of Ziemkiewicz free from stereotypical images and aimed at helping Polish identity to eliminate the colonial mentality.